Stratification of English as a Lingua Franca : Identity Constructions of Learners and Speakers - Josipović Smojver, Višnja (Array, 2013)
Studies of English as a Lingua Franca (ELF) suggest that some speakers of ELF are willing to mark their (national) identity in their ELF pronunciation, which we call the liberal stance, while others want to strive towards native models (e.g. Jenkins 2009), which we describe as the conservative stance . A recent study (Stanojević and Josipović 2010) confirms this, suggesting that liberalism vs. con-servativism towards ELF among Croatian university students is correlated with their major field of study. In this paper we show that there may be a more perva-sive process at play behind the liberal vs. conservative attitudes to ELF, namely identity construction. Based on the results of a questionnaire conducted among secondary school pupils, university students and employees of a company, we show that different attitudes to one’s own accent, the accent of one’s conversa-tional partners and teaching models primarily hinge on belonging to different groups of participants: learners vs. speakers of ELF. Our results support a non-monolithic, stratified ELF model, which allows changes in accordance with the needs and identity construction of its speakers.